'Jewish cricket': black-Jewish relations in Wondrous Oblivion (2003). Issue 3 (3rd July 2019) - Abrams, Nathan
ABSTRACT: This article explores Black-Jewish relations as presented through the prism of the 2003 film Wondrous Oblivion, directed by Paul Morrison. The film revisits the transition period between the 1950s and 1960s when Britain was starting to become a multicultural society. Set in South London in 1960, Wondrous Oblivion is a coming of age story focusing on David Wiseman (Sam Smith), a Jewish boy who aspires to be a first-class cricketer. David lives in an England still unmarked by significant racial difference and in a world of casual anti-Semitism. Through cricket, David is able to mimic the dominant norms of English society and successfully integrate but on his own terms which simultaneously resist the dominant values.